Curriculum based learning tools: project for year 6 human reproductive system / Siti Hajar Md. Jani and Dr. Jamali Wagiman - Md. Jani, Siti Hajar; Wagiman, Jamali (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Learning science can be both exciting and effective for primary school students. Teachers all over the world are taking advantage of diverse learning preferences and aptitudes. Among others, the use of visual aids and technology is frequently used to help students with their curriculum. Field trips, storytelling and analogies, group discussion, problem-based learning, role play and simulation require a lot of coordination between students and teachers. On the other hand, hands-on experiments, interactive demonstrations, and outdoor nature exploration may incur additional costs to conduct. Here, we would like to have a discussion concerning how we tried to apply visual aids in science classrooms for students in year six at Sekolah Kebangsaan Kuala Pilah. Hence, this approach uses visual aids to enhance classroom instruction, such as posters, diagrams, tools, and films, in class and on excursions with natural objects, practical demonstration of methods of operation (experiment, machine work, inclination patterns, theorem proofs, planning methods and annotations. Students interact in the activities of hearing, seeing, experiencing, reading, observing, and relating new information to previously learned and retained information that is required for the first level of knowledge acquisition.